2018
DOI: 10.5547/01956574.39.6.sdeb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Interconnection Project: Do Strategic Interactions Matter?

Abstract: High-Voltage Direct Current (HVDC) merchant transmission lines allow trade across separate power markets and often in different countries. Flows on existing cross-border lines are often assessed as suboptimal, which may be due to the light regulation that often prevails in these cases. This paper studies the impact of market power on HVDC interconnections as a determinant of imperfect arbitrage. We assess the impact of Physical Transmission Rights (PTRs) allocation on the management of an HVDC interconnection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We simplify the New York Control Area (NYCA) transmission representation (NYSRC, 2012) by treating flows to or from nodes outside of New York and Québec as exogenous parameters netted from consumption (Bushnell and Chen, 2012;Debia et al, 2018). Furthermore, given the "standard grouping" in Figure 1, we treat New York zones A-E and G-I as single nodes in order to obtain the stylized six-node network in Figure 2.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We simplify the New York Control Area (NYCA) transmission representation (NYSRC, 2012) by treating flows to or from nodes outside of New York and Québec as exogenous parameters netted from consumption (Bushnell and Chen, 2012;Debia et al, 2018). Furthermore, given the "standard grouping" in Figure 1, we treat New York zones A-E and G-I as single nodes in order to obtain the stylized six-node network in Figure 2.…”
Section: Datamentioning
confidence: 99%
“…Nasrolahpour et al (2016) examine how a merchant storage investor could affect market prices through its capacity-sizing decision as a Stackelberg leader in Alberta. The potential for other flexible technologies, such as combined heat and power plants (Virasjoki et al, 2018) and DC interconnections (Debia et al, 2018), to increase the leverage of strategic agents has been demonstrated in game-theoretic models of the Nordic and New York-Québec power systems, respectively. Nevertheless, even in such papers that bridge the physical realism of engineering-type models and the market realism of economic models, either hydro reservoirs or transmission flows are not modeled fully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis is closely related to the literature on local provision of public goods, starting with Williams (1966). 12 A recent contribution to this literature is Bloch and Zenginobuz (2007), who consider the impact of spillovers on the supply of public goods in a non-cooperative game between different governments in which spillovers may be symmetric or asymmetric and jurisdictions may differ in size; they conclude that the complexity of interactions will plague the design of institutions for multijurisdictional local public good economies with spillovers. A distinguishing feature of our model is that we assume that governments may be able to reach an efficient solution for the public good itself (the interconnector), but that overall optimality is not achieved because of the interaction (spillovers) between local networks and the interconnector.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on an analytical framework designed by Caillaud, Jullien and Picard (1996).11 Castaneda et al (2015) use empirical studies from behavioral economics and psychology to show that systems with independent regulatory agencies weaken the effects of political power, and diminish information asymmetries which improves sector performance 12. Other early contributions includeBrainard and Dolbear (1967) andBoskin (1973).…”
mentioning
confidence: 99%